Improved waterlogging tolerance of barley (Hordeum vulgare) by pretreatment with ethephon. (3rd April 2019) - Shiono, Katsuhiro; Ejiri, Masato; Shimizu, Kana; Yamada, Sumiyo
ABSTRACT: Root growth into hypoxic or anoxic waterlogged soil relies on internal aeration in plants. The plant hormone ethylene helps adapt to waterlogging by inducing the formation of aerenchyma, which provides a low-resistance pathway for the transport of oxygen from the shoot to the root apex. Waterlogging-susceptible crops including barley start to form aerenchyma after suffering waterlogging stress. But waterlogging can be fatal if aerenchyma formation is not fast enough. Here, we investigated whether pre-treating barley with ethephon, an ethylene-releasing agrochemical, could improve its tolerance to mimicked waterlogging conditions (using stagnant deoxygenated agar nutrient solution). In barley growing in aerated nutrient solution, ethephon treatment enhanced aerenchyma formation at the root tips and induced the development of shorter and shallower roots. Pre-treating barley leaves also delayed waterlogging-caused whiting and increased the percentages of viable root-tips under waterlogging conditions. However, the pretreatment did not noticeably increase fresh weight or shoot length. Further studies are needed to optimize ethephon treatment conditions to improve barley production under waterlogged conditions.